Medical planning (leaflet) - British Medical Association; Lucas Young, A.
1943-08 1943 1940s 7 pages MEDICAL PLANNING The Beveridge Plan for Social Security includes "a scheme for comprehensive health and rehabilitation services, for the prevention and cure of disease and the restoration of capacity for work, available to all members of the community." This is known as Assumption B. In view of the Government's adoption of the principle it is felt by the Medical Profession that the attitude of the public to this proposal should be sought. It is obvious that the interests of patient and doctor are identical, and any service introduced should satisfy both parties. Most people agree that some reform is due in the Nation's medical services, and the main question is what these reforms should be and how they are best brought about. It is with the object of ascertaining the views of the public that we ask your co-operation in answering the following questions and discussing them among your friends. 1. Do you insist on your right to choose your own doctor and to change your doctor as you see fit? 2. Are you in favour of the principle of private practice (including panel practice) in medicine as you know it at present, or do you think you would be better served by some form of State Medical Service? 3. If the latter, do you consider that your local Borough Council, which is a lay body, would be well fitted to organize and administer such a service within your district? 4. Would you agree to your family doctor being one of a team, working at and from a Health Centre? 5. Would you be prepared to see your doctor at a Health Centre instead of at his private house provided appointments could be fixed in order to avoid waiting ? 6. Do you think that the elimination of the competitive element from medical practice would have a good effect or the reverse? standard of services [P.T.O. 292/847/2/107